2014
DOI: 10.1080/14786419.2014.987142
|View full text |Cite
|
Sign up to set email alerts
|

Free radical-scavenging activities ofHomaliumspecies – An endangered medicinal plant of Eastern Ghats of India

Abstract: Three species of the genus Homalium - e.g. Homalium nepalense, Homalium tomentosum and Homalium zeylanicum (Flacourtiaceae) - are recorded in India which are confined to the Eastern Ghat hill ranges. While H. zeylanicum is the IUCN red-listed medium-sized tree, the other two are endangered species of medicinal significance. The antioxidant potential of leaf and bark of the plants was evaluated through successive extraction methods by using hexane, chloroform, ethyl acetate and methanol. The extracts were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Oxidative stress is believed to play a role in diabetes, inflammation, hepatotoxicity, and neurodegenerative diseases. The previous report of free radical scavenging and hepatoprotective activities of H. nepalense is thus supported with result of the current investigation of PM made through DPPH, ORAC, and CAP‐e assays [7,8]. Traditional uses of the bark of H .…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Oxidative stress is believed to play a role in diabetes, inflammation, hepatotoxicity, and neurodegenerative diseases. The previous report of free radical scavenging and hepatoprotective activities of H. nepalense is thus supported with result of the current investigation of PM made through DPPH, ORAC, and CAP‐e assays [7,8]. Traditional uses of the bark of H .…”
Section: Resultssupporting
confidence: 70%
“…After incubation, absorbance was measured at 517 nm in microplate reader (Synergy H1MF, BioTek, USA). Ascorbic acid was used as the standard drug and results were expressed as IC 50 (µg/mL) [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently comprising over 70 accepted species listed on The Plant List database (version 1.1 2020; http://www.theplantlist.org), Homalium is a genus of deciduous medium-sized trees with a predominant distribution in temperate and subtropical regions [1]. Several members of the genus have been reported due to their use in folk medicine, but data on the pharmacological properties are generally scant.…”
Section: Introductionmentioning
confidence: 99%
“…Ethnobotanical surveys revealed that some Homalium species are used as wound healing remedies; Homalium zeylanicum Benth. is generally referred to as a wound healing plant [1,5]; leaves from Homalium foetidum Benth. are used by tribes from Papua New Guinea to treat topical ulcers and subcutaneous skin infections [2,6].…”
Section: Introductionmentioning
confidence: 99%